The expression `19/22 + (-1/2)` has to be expressed in the simplest form.

`19/22 + (-1/2)`

open the brackets

=> `19/22 -1/2`

make the denominator the same for both the terms

=> `19/22 - 11/22`

=> `(19 - 11)/22`

=> 8/22

=> 4/11

**The expression `19/22 + (-1/2)` is equal to **`4/11`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now